2020
DOI: 10.1111/ejh.13401
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib‐induced hemolysis is noticeably common but rarely shows features of thrombotic microangiopathy: A retrospective study

Abstract: Objective Hemolysis is a sporadically reported but potentially serious side effect of the proteasome inhibitor carfilzomib. We aimed to investigate the frequency of hemolysis in an unselected cohort. Methods We performed a retrospective, single‐center study of the incidence of hemolysis in patients treated with carfilzomib, based mainly on consecutive haptoglobin levels. The patients were diagnosed with myeloma (n = 20), AL amyloidosis (n = 3), and light‐chain deposition disease (n = 1). Carfilzomib treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 25 Isolated microangiopathic hemolytic anemia, without all the features of a full-blown TMA, was observed at very high rates in carfilzomib-treated patients in a recent case series where it occurred in 16 out of 24 patients (67%). 26 In this single-center cohort, 11 out of 16 patients had mild hemolysis with haptoglobin <0.1 g/L but no transfusion requirement; 5 out of 16 required transfusion, and 1 patient had a severe and subsequently fatal TMA. 26 Cases of TMA have also been reported with the newer generation of PIs such as ixazomib.…”
Section: How We Investigate Maha In a Cancer Patientmentioning
confidence: 78%
See 1 more Smart Citation
“… 25 Isolated microangiopathic hemolytic anemia, without all the features of a full-blown TMA, was observed at very high rates in carfilzomib-treated patients in a recent case series where it occurred in 16 out of 24 patients (67%). 26 In this single-center cohort, 11 out of 16 patients had mild hemolysis with haptoglobin <0.1 g/L but no transfusion requirement; 5 out of 16 required transfusion, and 1 patient had a severe and subsequently fatal TMA. 26 Cases of TMA have also been reported with the newer generation of PIs such as ixazomib.…”
Section: How We Investigate Maha In a Cancer Patientmentioning
confidence: 78%
“… 26 In this single-center cohort, 11 out of 16 patients had mild hemolysis with haptoglobin <0.1 g/L but no transfusion requirement; 5 out of 16 required transfusion, and 1 patient had a severe and subsequently fatal TMA. 26 Cases of TMA have also been reported with the newer generation of PIs such as ixazomib. 27 …”
Section: How We Investigate Maha In a Cancer Patientmentioning
confidence: 78%
“…A recent analysis by Kozlowski et al (2020) showed that haemolysis in carfilzomib-treated patients is indeed common, although often mild [ 10 ]. The rate of haemolysis reported in that study was somewhat higher, perhaps due to our use of strict multi-point criteria.…”
mentioning
confidence: 99%